Animal Model of Acid-Reflux Esophagitis: Pathogenic Roles of Acid/Pepsin, Prostaglandins, and Amino Acids. (2nd February 2014) - Takeuchi, Koji; Nagahama, Kenji
Abstract : Esophagitis was induced in rats within 3 h by ligating both the pylorus and transitional region between the forestomach and glandular portion under ether anesthesia. This esophageal injury was prevented by the administration of acid suppressants and antipepsin drug and aggravated by exogenous pepsin. Damage was also aggravated by pretreatment with indomethacin and the selective COX-1 but not COX-2 inhibitor, whereas PGE2 showed a biphasic effect depending on the dose; a protection at low doses, and an aggravation at high doses, with both being mediated by EP1 receptors. Various amino acids also affected this esophagitis in different ways; L-alanine and L-glutamine had a deleterious effect, while L-arginine and glycine were highly protective, both due to yet unidentified mechanisms. It is assumed that acid/pepsin plays a major pathogenic role in this model of esophagitis; PGs derived from COX-1 are involved in mucosal defense of the esophagus; and some amino acids are protective against esophagitis. These findings also suggest a novel therapeutic approach in the treatment of esophagitis, in addition to acid suppressant therapy. The model introduced may be useful to test the protective effects of drugs on esophagitis and investigate the mucosal defense mechanism in the esophagus.